A highly curable lymphoma occurs preferentially in the proximal tibia of young patients - Subik, M Kristina; Herr, Megan M; Hutchison, Robert E; Kelly, Jennifer; Tyler, Wakenda K; Merzianu, Mihai; Burack, W Richard (Modern pathology, 2014)
The presentation of two 19-year-old male subjects with stage I non-Hodgkin lymphoma in the proximal tibia prompted an extensive review of institutional and national databases to assess whether there is any statistical evidence that these reflected a previously overlooked syndromic pattern of presentation. The institutional records of a single institution were reviewed for presentation of non-Hodgkin lymphoma in the bone. The records of two additional institutions were reviewed for all reports of non-Hodgkin lymphoma in the tibia. Analysis was performed on data from Surveillance, Epidemiology, and End Results (SEER) dichotomized to bone presentation in the lower extremity versus other bones. Institutional databases included 20 patients with tibial presentation of lymphoma with a median age of 22.5 years (versus 42 for all bone lymphomas; P<0.001). Eighteen out of twenty patients had diffuse large B-cell lymphoma, and all patients aged ≤40 achieved remission and apparent cure. Distinctive and unusual features were a tendency for bilateral involvement of the tibia and sclerotic changes on X-ray. SEER data included 808 cases of bone lymphoma; the fraction of cases presenting in the lower extremity versus other bone sites is higher at ages ≤40 years (38% versus 19%; P<0.0001). Presentation in the lower extremity, as compared with other bone sites, confers 97% overall survival in patients aged ≤40 (versus 82%; P=0.01). This survival effect was independent of stage. In contrast, no significant difference in overall survival was identified for lower extremity versus non-lower extremity site for age >40. These data show a previously undescribed syndromic pattern of disease presentation: bone lymphoma in young patients is likely to present in the lower extremity—specifically the proximal tibia—has atypical sclerotic features on X-ray, is often bilateral, and has an excellent prognosis compared with bone lymphomas at other sites matched for stage and age.